Systematics and distribution of the subfamily chalcophorinae (coleoptera : buprestidae) of Sarawak - Ratnawati, Binti Hazali (Universiti Malaysia Sarawak (UNIMAS), 2005)
A total of approximately 46 species from nine genera representing two tribes of Chalcophorinae (Coleoptera: Buprestidae) is known to occur in Sarawak. The tribe Chalcophorini with 44 species (97% of total species) represented the most diverse tribe residing as voucher specimens in the Sarawak Museum and the Unimas Insect Collections. In terms of the number of genera, the tribe Chalcophorini constitutes 89% (8 genera) of the subfamily CbaIcophorinae while the tribe Psilopterini consists of II % (I genus). In this study, a total of 19 species in eight genera of Chalcophorinae were evaluated. A systematic account ofeach species is provided and the keys to the genera and species were presented. Among the Chalcophorinae in Sarawak, Iridolaenia mirabilis was found to be the most abundant species with 20 individuals (21 % of the total individuals) represented in voucher collections. Most of the species of Chalcophorinae known to occur in Sarawak were found in peat swamp forest. Chrysochroa daleni, C. lacordairei, Cyalilhus rugifrons and Chrysodema smaragdula could be considered as the rarest species of buprestid in Sarawak being represented by one individual each. Distribution mapping of the species shows that the Chalcophorinae of Sarawak is distributed throughout the state. However, most species were associated with peat swamp forest.